The comparative study on the digital economy and trade between China, the U.S. and the EU (Journal of Information Technology and Data Management, 2022)
The development of digital economy and expansion of digital trade has become an inherent requirement for China to seize the high ground of digital industry revolution, and to build a new development pattern in which the domestic circulation is the mainstay and the domestic and international double circulation promote each other. Clarifying China’s position, especially its advantages and disadvantages relative to the USA and the EU in the international competition of digital economy and trade, is crucial to judge and guide the future development of China’s digital economy in both domestic and international double circulation. At present, there are various methods to define and measure the digital economy and digital trade, but there is a lack of connection and comparison between different methods as well as between different countries from a global perspective. Based on the solid statistical measurements and comparative analysis of relevant data，we make in-depth research on scale pattern, structural pattern, dynamic pattern, competition pattern, dependency pattern, etc. between China, the USA and the EU, and find that China’s digital economy and trade is“big but not excellent, fast but not first, surplus but not winning”. Therefore, we propose policy suggestions for the sustainable development of China’s digital economy and trade such as comprehensively optimizing the digital economic structure, promoting strengths and avoiding weaknesses in the electronic equipment manufacturing industry, cultivating a new pillar of the information service industry, and reversing the disadvantages in the digital media industry.